2010
DOI: 10.3390/ijerph7030784
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Exercise Benefits and Barriers of Non-Exercising Female University Students in the United Kingdom

Abstract: Many individuals do not engage in sufficient physical activity due to low perceived benefits and high perceived barriers to exercise. Given the increasing incidence of obesity and obesity related health disorders, this topic requires further exploration. We used the Exercise Benefits/Barriers Scale to assess perceived benefit and barrier intensities to exercise in 200 non-exercising female university students (mean age 19.3 years, SD = 1.06) in the UK. Although our participants were selected because they self … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
120
6
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(160 citation statements)
references
References 22 publications
25
120
6
9
Order By: Relevance
“…According to our study, the Appearance and Social indices recorded low values, a fact confirmed in another study [31], which concluded that it is precisely these two indicators that set up the motivational profile of PA practice. Factors of improving quality of life and social interaction can be explained by the nature of our subjects who, due to life in the university, may have a number of opportunities to relate, and this may reduce awareness of social benefits due to PA practice [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our study, the Appearance and Social indices recorded low values, a fact confirmed in another study [31], which concluded that it is precisely these two indicators that set up the motivational profile of PA practice. Factors of improving quality of life and social interaction can be explained by the nature of our subjects who, due to life in the university, may have a number of opportunities to relate, and this may reduce awareness of social benefits due to PA practice [32].…”
Section: Discussionmentioning
confidence: 99%
“…Kondrič [34], found that the latent structure of motivation for student participation in sports contains six factors: socialization, popularity, fitness, and health, social status, sporting events, and relaxation through sport. Some authors [28,32,34] consider that the education process on physical exercise in students has a motivational structure that is defined by three motivational factors: enjoyment, body modeling to improve physical appearance, and socializing with friends.…”
Section: Discussionmentioning
confidence: 99%
“…Já no Reino Unido, a preguiça foi tida como a principal barreira 15 . Diferenças nos resultados destes estudos podem estar relacionadas com as características de cada região, principalmente no que se refere ao contexto sociocultural e econômico, o qual cada amostra encontra-se inserida 18 .…”
Section: Discussionunclassified
“…The validity related to the construct was analyzed through the investigation of associations among the EBBS results and the evaluation of personal and clinical aspects that, according to literature, are capable of interference in the knowledge of the benefits and realization of the physical exercise (12,14,15) aiming to detect the interference of these on the EBBS result. The variables investigated were: socio-demographic (age, level of education, marital status, occupation, with whom one lives and income), anthropometric and physiological (weight, height, BMI -Body Mass Index, blood pressure), biochemical (random glucose level), lifestyle (active, sedentary, regular physical activity practice, smoking, alcohol consumption, limitations for mobility), morbidities (chronic degenerative pathologies) and falls.…”
Section: Actamentioning
confidence: 99%
“…It has been widely used by American, European and Asian researchers (12)(13)(14) . The EBBS was prepared based on the Health Promotion Model (HPM), which assesses the activities focused on the development of resources which maintain or intensify the well-being, for example, the physical activity.…”
Section: Introductionmentioning
confidence: 99%